ICTforAg+ Mexico “Cultivating Inclusion” - Gardeazabal Monsalve, Andrea; Bert, Federico; Garcia, David (CGIAR, 2023)
The annual ICTforAg conference brings together global experts to address digital solutions for challenges in agri-food systems in low and middle-income countries. Along with the 2023 virtual event, titled “Cultivating Inclusion” a dedicated Latin America in-person chapter was held at the CIMMYT campus. Hosted by IICA, CGIAR Digital Innovation, and CGIAR AGRILAC, the event had 49 participants from 7 countries, representing diverse sectors such as agtechs, governments, local research institutes, and financial organizations. Three insightful panel discussions explored Responsible Digital Innovation, Digital Transformation in Agroindustry, and Digital Innovation in Agricultural Research, addressing adoption gaps, user perspectives, ethics, and inclusion. A significant outcome of the workshop was a dynamic discussion on collaborative opportunities, leading to three key initiatives: collaborative research on limiting factors for digital innovation in South America, a data-sharing platform in Central America, and a service value chain for farmers enabled by digital technologies in Colombia and Mexico.